2018
DOI: 10.1080/13880209.2018.1479868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of garlic polysaccharide on alcoholic liver fibrosis and intestinal microflora in mice

Abstract: Context: Alcoholic liver fibrosis (ALF) is treatable and reversible consequence of liver disease. Intestinal microflora plays an important role in the progression of liver disease. Garlic (Allium sativum L. [Amaryllidaceae]) has been consumed as a traditional medicine to treat liver injury.Objective: To investigate the effects of garlic polysaccharide (GP) on ALF and intestinal microflora in mice.Materials and methods: KM mice were orally administered with alcohol (56%, 6 mL/kg) for 30 d to establish ALF model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 31 publications
(31 reference statements)
0
36
1
1
Order By: Relevance
“…f-Lachnospiraceae has been reported to be associated with anti-inflammatory activity [18], host mucosal integrity [19], the consumption of energy and the level of leptin [20]. Fructan [21,22] and whole garlic [23] have been reported to increase the abundance of f-Lachnospiraceae, but alliin was found to decreased it [24]. In particular, the relative abundance of g-Akkermansia decreased by aging and HFD diet, and increased by 5% AFG supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…f-Lachnospiraceae has been reported to be associated with anti-inflammatory activity [18], host mucosal integrity [19], the consumption of energy and the level of leptin [20]. Fructan [21,22] and whole garlic [23] have been reported to increase the abundance of f-Lachnospiraceae, but alliin was found to decreased it [24]. In particular, the relative abundance of g-Akkermansia decreased by aging and HFD diet, and increased by 5% AFG supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…It contains high levels of potassium, phosphorus zinc, and sulfur, moderate levels of selenium, calcium, magnesium, manganese, iron, and low levels of sodium, vitamin A and C and B-complex [ 18 ]. In the last years, considerable attention has been given to its main bioactive compounds, particularly polyphenols, flavonoids, flavanols, tannins [ 5 , 19 ], saponins [ 4 ], polysaccharides [ 6 ], sulfur-containing compounds (including alliin, allicin, ajoene, allylpropyl disulfide, DATS, S-allylcysteine, vinyldithiins, SAMC), enzymes (like allinase, peroxidase, myrosinase), and other compounds, such as β-phellandrene, phellandrene, citral, linalool, and geraniol [ 3 ]. There are more than twenty well-known polyphenolic compounds in garlic, including kaempferol 3,7-di- O -rhamnoside, kaempferol-3 glucuronide, kaempferol-3- O -glucoside, kaempferol-3- O -beta- d -glucoside-7- O -alpha- l -rhamnoside, luteoline, and apigenine [ 20 ].…”
Section: Bioactive Compounds Of Garlicmentioning
confidence: 99%
“…In 1550 B.C., antibiotics and pharmacy products were not available so garlic was used for medicinal purposes in different epidemics, such as typhus, dysentery, cholera, and influenza [ 2 ]. The therapeutic effects of garlic are mainly due to the impressive activity of its bioactive compounds, such as organic sulfides [ 3 ], saponins [ 4 ], phenolic compounds [ 5 ], and polysaccharides [ 6 ]. For example, several in vitro and in vivo studies have showed that garlic compounds are able to modulate various signaling pathways, including nuclear factor-κB and wingless-related integration site [ 7 ], matrix metalloproteinases, nuclear factor erythroid 2 like 2, protein kinase B (pAkt), mitogen-activated protein kinase, c-Jun N-terminal kinases, caspases, p38, transforming growth factor beta 1 (TGF-β1), TGF-β type II receptor, psmad2/3, smad4 and smad7 [ 8 , 9 ], cytokines, intercellular adhesion molecule [ 10 ], notch pathway [ 11 ], 5’ AMP-activated protein kinase pathway [ 12 ], vascular endothelial growth factor [ 13 ], cyclooxygenase 2, inducible nitric oxide synthase, Akt/mTOR [ 14 ], and Keap1 [ 15 ], leading to improved anti-inflammatory and antioxidant properties, as well as chemopreventive, antiproliferative, anti-angiogenic, antidiabetic, and cardioprotective effects.…”
Section: Introductionmentioning
confidence: 99%
“…Animals and humans exposed to alcohol chronically exhibit overgrowth of opportunistic pathogenic and depletion of beneficial intestinal bacteria. Lactobacillus, Clostridium butyricum and Bacteroides decreased in diabetic liver injury mice [81].…”
Section: Pathophysiology Of Alcoholic Liver Diseasementioning
confidence: 89%